Eleanor Roosevelt at the United Nations: “Diplomacy from Below” and the Search for a New Transatlantic Dialogue - Raffaella Baritono (European Journal of American Studies)
In 1945, Truman appointed Eleanor Roosevelt as a member of the American delegation to the first session of the United Nations in an effort to send a signal to the many associations who wanted to have a role in the redefinition of the post-war democratic order. ER’ s commitment to peace and social justice was an expression of internationalism ‘from below’, which was convinced that the challenge to enlarge and make democracy more inclusive, more respectful of gender, racial, and ethnic differences had to be won not only in the domestic political sphere but also in the international one. The paper will explore the intrinsic contradiction which was at the root of ER’ s engagement in the UN. On the one hand, she was conscious of her official status as American officer and the symbol of the American democratic model; on the other, her will to give expression and voice to the questions posed by American and European civic associations and their commitment to democracy, social justice and human rights in the growing Cold War climate provoked tensions and ambiguities that proved difficult to solve.